2022
DOI: 10.3389/fcvm.2022.822209
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Dietary Vitamin Intake Time Across a Day With Cardiovascular Disease and All-Cause Mortality

Abstract: BackgroundChrono-nutrition emphasized the importance of the intake time; however, less is known about the impact of dietary vitamin intake time on health. This study aimed to examine our hypothesis about which vitamin intake time could influence the natural course of cardiovascular disease (CVD).MethodsA total of 27,455 adults enrolled in the National Health and Nutrition Examination Survey (NHANES) during 2003–2014 were recruited. The 12 dietary vitamin intakes in the morning, afternoon, and evening were cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
2
2
0
Order By: Relevance
“…Our findings are supported by a previous study that investigated the potential negative association of meal timing of individual antioxidants on mortality [20]. The optimal intake times of dietary antioxidants vitamin C and vitamin E were in the evening, which was associated with the lowest risks of CVD and all-cause mortalities [20]. Notably, we further found that after including coffee, the inverse associations between total, dinner and Δ DACs and all-cause mortality weakened or was even lost, while an inverse association between breakfast DAC and allcause mortality was observed.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings are supported by a previous study that investigated the potential negative association of meal timing of individual antioxidants on mortality [20]. The optimal intake times of dietary antioxidants vitamin C and vitamin E were in the evening, which was associated with the lowest risks of CVD and all-cause mortalities [20]. Notably, we further found that after including coffee, the inverse associations between total, dinner and Δ DACs and all-cause mortality weakened or was even lost, while an inverse association between breakfast DAC and allcause mortality was observed.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, this study is the first to examine the association of meal timing of DAC with all-cause and specific-cause mortality and to emphasize the importance of DAC distribution for a low risk of mortality. Our findings are supported by a previous study that investigated the potential negative association of meal timing of individual antioxidants on mortality [ 20 ]. The optimal intake times of dietary antioxidants vitamin C and vitamin E were in the evening, which was associated with the lowest risks of CVD and all-cause mortalities [ 20 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Folate is a water-soluble B vitamin derived from foodstuffs and participates in various biochemical processes, espe-cially via its central role in the metabolism of nucleotides for DNA synthesis and methylation reaction [1]. Folate deficiency is linked to an increased risk of cardiovascular diseases, Alzheimer's disease, and certain cancers [2][3][4]. Folic acid (FA) is a synthetic form of folate and is administered as a dietary supplement.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Observational data has also suggested that adequate intake of iron, potassium, magnesium, vitamin E, vitamin C, vitamin B6, and folate could lower the risk of CVD. [5][6][7][8][9][10] However, the precise relationship between micronutrients and their role in preventing or reducing the risk of CVD is still not fully understood. A systematic review from 2018 suggested that, apart from B vitamins, the intake of micronutrients may not significantly impact CVD risk.…”
Section: Introductionmentioning
confidence: 99%